Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.7 - Simplifying Complex Fractions - Exercise Set: 6

Answer

$\dfrac{\dfrac{6x-3}{5x^{2}}}{\dfrac{2x-1}{10x}}=\dfrac{6}{x}$

Work Step by Step

$\dfrac{\dfrac{6x-3}{5x^{2}}}{\dfrac{2x-1}{10x}}$ Evaluate the division: $\dfrac{\dfrac{6x-3}{5x^{2}}}{\dfrac{2x-1}{10x}}=\dfrac{6x-3}{5x^{2}}\div\dfrac{2x-1}{10x}=\dfrac{(6x-3)(10x)}{(5x^{2})(2x-1)}=...$ Take out common factor $3$ from the first parentheses of the numerator and simplify: $...=\dfrac{3(2x-1)(10x)}{(5x^{2})(2x-1)}=\dfrac{3(10x)}{5x^{2}}=\dfrac{3(2)}{x}=\dfrac{6}{x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.